Comparative analysis of state support for agricultural producers in Russia and in the world - A. V. Loseva; A. V. Fedosinа; E. V. Dupliy (Управление)
Despite numerous trade disputes within the World Trade Organization (WTO) regarding the overestimation of the support level for agriculture by individual countries of the world, subsidizing farmers by their own governments not only does not decrease, but also tends to increase in general. In the conditions of the WTO member countries open markets, the world countries food security, including Russia, largely depends not only on the competitiveness of their own agriculture, but also on the support of their own agricultural sector commensurate with other states. Based on this, it is an urgent task to track the scale of state influence on the industry in other countries in order to avoid excessive competition of imported products. Thus, the purpose of the article is to study the dynamics of state support for agriculture in the countries of the world based on the Organization for Economic Cooperation and Development (OECD) data. The results of the work are detailed information on the comparative level of state support for the agro-industrial complex in the countries of the world, and the amount of support for the Russian agricultural industry corresponds to the world average. To process the information received in order to present the results of the work as accessible as possible, tabular and graphical methods are used.